Benefits of dense labour markets: Evidence from transitions to employment in Germany - Silke Hamann; Annekatrin Niebuhr; Jan Cornelius Peters (Kiel University, Department of Economics, 2016)
We analyse whether the size of the local labour market allows for better matching between job seekers and vacancies, which is thought to enhance productivity. This analysis is based on a large data set providing detailed micro-level information on new employment relationships in Germany. Our results suggest rather small matching benefits. Doubling employment density increases the productivity of new employment relationships by 1.1% to 1.2%. Moreover, the findings indicate that the benefits accrue only to persons experiencing job-to-job transitions and short-term unemployed. We detect no important impact of agglomeration on transitions from long-term non-employed.
Keywords: R23; J31; 330; agglomeration economies; matching; urban wage premium; transitions to employment